Europeana in Linked Open Data: Semantic Web concepts in applied dimension of the Digital Humanities - Coneglian, Cabo Saraiva [UNESP]; Santarem Segundo, Jose Eduardo [UNESP] (Univ Federal Santa Catarina, 2017)
The emergence of new technologies, has introduced means for the dissemination and availability of information more efficiently. An initiative, called Europeana, has been promoting this adaptation of information objects in the Web, and more specifically in Linked Data. Thus, this study aims to present a discussion on the relationship between the Digital Humanities and the Linked Open Data within the context of the Europeana. To do this, we use an exploratory methodology and seeks to explore issues related to the Europeana Data Model, EDM, through SPARQL. As a result, we understand the characteristics of the EDM by using SPARQL. We identified also the importance that the concept of Digital Humanities has within the context Europeana.
Keywords: Semantic web; Linked open data; Digital humanities; Europeana; EDM